(untitled) (Journal of Institute of Science and Technology, 2017)
The area affected by sinkholes in Thulibeshi Phat of Armala VDC, Pokhara was studied in order to understand natural settings of the study area. A total of 117 sinkholes from depth range of 1 to 5 m and diameters from 1 to 15.2 m were observed at the time of our field visit. Out of these sinkholes, 52 sinkholes were filled sinkholes, 12 were water-bearing sinkholes and others were opened sinkholes. The area consists of sediments of fluvio-lacustrine and debris deposits and the sinkhole site has sediments mainly of silt, clay and fine sand size with chemical compositions of kaolin of major silica and minor constituents of calcium carbonate. The main mechanism of formation of sinkholes in Thulibeshi Phat was washed-away effect generated by piping mechanism of fine sediments by sub-surface flowing water, which was initiated by partial dissolution of carbonate containing sediments. Human impact on landscape, especially land use changes and stream channel modifications accelerated the process of piping mechanism for initiating and extending the sinkhole affected area in the present study site. This study will help to understand how geological conditions and human impacts interact to form sinkhole hazards in Nepal. Journal of Institute of Science and Technology, 2017, 22 (1): 17-24